Desenvolvimento de habilidades motoras em crianças de projetos sociais da cidade de Bauru - Brito, Matheus Belizário [UNESP] (2015)
The childhood is a period in which there are a lot of changes in the various fields of human development. For a complete motor development, several studies show that it is necessary that the child is constantly engaged in different activities at different environments, enabling it an accumulation of experiences in different situations. So it is extremely important to study how this process takes place in the development of motor skills in children and what factors can interfere with this process. Terefore, the aim of the study was to identify the motor profile of 10 to 11 years-old children who participate in the UNESP Extension programs. For thas, 21 children participated in the study who performed the Test of Gross Motor Development (TGMD - 2). The results demonstrated that the conditions offered by the social projects context and by extension programs, experienced over the years, seems to influence and provide different levels of motor development for children; however, more participation could bring further benefits in refinement of motor skill.